Respuesta :
We are dividing the polynomial [tex]2x^{2} +13x+26[/tex] by x+4
notice that [tex]2x^{2}[/tex] is x times 2x,
so if we multiply (x+4) by 2x, which gives us [tex]2 x^{2} +8x[/tex], we can 'separate' one [tex]2 x^{2} +8x[/tex] from [tex]2x^{2} +13x+26[/tex] to get the following simplification:
[tex] \frac{2x^{2} +13x+26}{x+4}= \frac{ 2x^{2}+8 x}{x+4} + \frac{5x+26}{x+4}=2x+ \frac{5x+26}{x+4}[/tex]
similarly we notice that 5x is x times 5, so if we multiply (x+4) by 5, we get 5x+20 so we can rewrite
[tex]\frac{5x+26}{x+4}= \frac{5x+20}{x+4}+ \frac{6}{x+4}=5+\frac{6}{x+4}[/tex]
[tex]\frac{6}{x+4}[/tex] can not be simplified any further since the degree of 6, is smaller than the degree of x+4
combining our work, we have:
[tex]\frac{2x^{2} +13x+26}{x+4}=2x+5+\frac{6}{x+4}[/tex]
Answer:
q(x)= 2x+5
r(x)=6
b(x)=x+4
Remark: we can solve the problem by long division or the division algorithm as well.
notice that [tex]2x^{2}[/tex] is x times 2x,
so if we multiply (x+4) by 2x, which gives us [tex]2 x^{2} +8x[/tex], we can 'separate' one [tex]2 x^{2} +8x[/tex] from [tex]2x^{2} +13x+26[/tex] to get the following simplification:
[tex] \frac{2x^{2} +13x+26}{x+4}= \frac{ 2x^{2}+8 x}{x+4} + \frac{5x+26}{x+4}=2x+ \frac{5x+26}{x+4}[/tex]
similarly we notice that 5x is x times 5, so if we multiply (x+4) by 5, we get 5x+20 so we can rewrite
[tex]\frac{5x+26}{x+4}= \frac{5x+20}{x+4}+ \frac{6}{x+4}=5+\frac{6}{x+4}[/tex]
[tex]\frac{6}{x+4}[/tex] can not be simplified any further since the degree of 6, is smaller than the degree of x+4
combining our work, we have:
[tex]\frac{2x^{2} +13x+26}{x+4}=2x+5+\frac{6}{x+4}[/tex]
Answer:
q(x)= 2x+5
r(x)=6
b(x)=x+4
Remark: we can solve the problem by long division or the division algorithm as well.